KULTUR PESANTREN: RELASI KIAI, SANTRI, DAN KITAB KUNING - Fatoni, Nur (IBDA` : Jurnal Kajian Islam dan Budaya, 2011)
This article describes the boarding school culture which focuses on the relation among Islamic scholar, students at Muslim school, and kitab kuning. The data colleting method which is used in this research are observation, interview and documentation. This article shows that the soul of Islamic boarding school is the Islamic scholar and the supporting factors are students and kitab kuning. This combination is inseparable. The Islamic scholar responds the modernity by teaching that holy books in some levels based on the students’ ability.